Multi-child families in Poland – demographic and social characteristics - Pawlus, Małgorzata (Chrześcijaństwo-Świat-Polityka, 2025)
This article aims to provide a demographic and social overview of multi-child families over the last two decades, based on available data. It will present trends relating to large families and changes to their numbers and structures, based on information obtained from the last three National Censuses (2002, 2011 and 2021). Referring to Bożenna Balcerzak–Paradowska’s concept of ‘large families as an environmental characteristic’, key changes in the situation of multi-child families will be highlighted. Changes in parents’ education, income and risk of poverty confirm that multi-child families are evolving in nature and diversity.